Eksploitasi Lingkungan oleh Kampus: Tinjauan HR. Bukhari No. 479 dan RUU Minerba Pasal 51A - Mohammad Ghozali; Tajul Arifin (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The policy of granting Mining Business Licenses (IUP) to universities under Article 51A of the Minerba Bill raises legal, ethical, and sustainability concerns. This study applies a qualitative approach through literature review to examine the provision from the perspectives of Indonesian law and Islamic teachings. The findings reveal that allowing universities to manage mining permits risks diminishing their academic role, compromising scholarly independence, and fostering potential conflicts of interest. From the standpoint of positive law, this policy contradicts the precautionary principle, social justice, and educational objectives enshrined in the 1945 Constitution, the Higher Education Law, and the Environmental Protection Law. In Islamic thought, irresponsible exploitation of natural resources is classified as fasād (corruption), strictly prohibited, as reflected in Hadith No. 479 narrated by Bukhari. The study concludes by rejecting the provision and recommends repositioning universities as guardians of sustainability values rather than participants in extractive industries.